Nutritional status and impact on outcomes of patients with locally advanced head and neck squamous cell carcinoma treated with concurrent chemoradiotherapy: a pre-planned secondary analysis of a phase 3 randomized controlled trial - Vanita Noronha; Avani Chawda; Vijay Patil; Nandini Menon; Minit Shah; Supriya Goud; Sucheta More; Srushti Shah; Vijayalakshmi Mathrudev; Kumar Prabhash (Journal of the Egyptian National Cancer Institute)
Abstract Background Adequate nutrition can mitigate side-effects and improve recovery for patients with locally advanced head-and-neck squamous cell cancer (LAHNSCC), while malnourishment can increase morbidity and mortality. We aimed to evaluate the baseline nutritional status of patients with LAHNSCC planned for curative chemoradiotherapy (CRT), the evolution of nutritional status during the course of CRT and to assess whether nutrition impacted their clinical outcomes. Methods This was a pre-planned secondary analysis of a Phase III randomized controlled trial conducted between 2013 and 2017 in 300 patients with LAHNSCC who were randomly assigned to receive either cisplatin 30 mg/m2 once-a-week or 100 mg/m2 once-in-3-weeks concurrently with radiation. This analysis included 112 patients for whom nutritional parameters were recorded. Patient Generated Subjective Global Assessment (PG-SGA) forms were used to evaluate malnutrition severity at different treatment stages. Scores on the PG-SGA ranged from 0 to 35, with higher scores denoting greater malnutrition. Scores were grouped, with 0–3 indicating normal to mild malnutrition, and ≥ 4 denoting moderate to severe malnutrition. Baseline scores were compared with subsequent scores and survival outcomes were analyzed. Results At baseline assessment, 42.8% of patients had normal to mild malnutrition, while 57.1% had moderate to severe malnutrition. There were higher baseline malnutrition rates in women, users of smokeless tobacco, and patients with buccal mucosa tumors. By day 21 of treatment, 44 (56.4%) patients had moderate to severe malnutrition, while 34 (43.6%) had normal nutrition or mild malnutrition. Among those with moderate to severe malnutrition at baseline, 13 (29.5%) patients had an improvement in their nutritional status, while 14 (41.2%) patients with normal to mild nutrition at baseline had deterioration in their nutritional status during the course of CRT. Baseline nutritional status did not significantly impact progression-free, locoregional relapse-free or overall survivals. Conclusions Pre-treatment nutrition is crucial for managing weight and reducing treatment complications in patients with LAHNSCC. Over 40% of patients with normal baseline nutrition have deterioration of their nutritional status during CRT. We were unable to find any correlation between nutrition and clinical outcomes in patients with LAHNSCC receiving curative CRT. Larger studies are needed to explore the impact of nutrition on treatment outcomes, emphasizing regular dietary assessments and interventions to improve patient compliance. Trial registration Clinical Trial Registry of India, under the registration number CTRI/2012/10/003062.